Premixed Combustion of Coconut Oil on Perforated Burner - I.K.G. Wirawan; I.N.G. Wardana; Rudy Soenoko; Slamet Wahyudi (International Journal of Renewable Energy Development, 2013)
Coconut oil premixed combustion behavior has been studied experimentally on perforated burner with equivalence ratio (φ) varied from very lean until very rich. The results showed that burning of glycerol needs large number of air so that the laminar burning velocity (SL) is the highest at very lean mixture and the flame is in the form of individual Bunsen flame on each of the perforated plate hole. As φ is increased the  SL decreases and the secondary Bunsen flame with open tip occurs from φ =0.54 at the downstream of perforated flame. The perforated flame disappears at φ = 0.66 while the secondary Bunsen flame still exist with SL increases following that of hexadecane flame trend and then extinct when the equivalence ratio reaches one or more. Surrounding ambient air intervention makes SL decreases, shifts lower flammability limit into richer mixture, and performs triple and cellular flames. The glycerol diffusion flame radiation burned fatty acids that perform cellular islands on perforated hole.  Without glycerol, laminar flame velocity becomes higher and more stable as perforated flame at higher φ. At rich mixture the Bunsen flame becomes unstable and performs petal cellular around the cone flame front.